2022
DOI: 10.1080/21655979.2022.2079253
|View full text |Cite
|
Sign up to set email alerts
|

Stearoyl-CoA desaturase 1 regulates malignant progression of cervical cancer cells

Abstract: The primary regulatory gene for fatty acid synthesis, stearoyl-CoA desaturase 1 (SCD1), has been linked to the progression of several malignancies. Its role in cervical cancer remains unclear till now. This paper aimed to explore the role and mechanism of SCD1 in cervical cancer. The GEPIA database was used to perform a bioinformatics analysis of the role of SCD1 in cervical cancer staging and prognosis. The influences of SCD1 knockdown on cell proliferation, migration, invasion, and epithelial-mesenchymal tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Studies have confirmed that many tumors, such as gastric and colorectal cancer, have a high expression of GSK3β 47 . In addition, a large number of studies have shown that in CC, GSK3β is involved in the regulation of the PI3K/Akt signaling pathway and the promotion of the malignant progression of CC cells 48,49 . This suggests that the regulatory role of USP14 in CC progression may be due to interactions with different key signaling pathways.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Studies have confirmed that many tumors, such as gastric and colorectal cancer, have a high expression of GSK3β 47 . In addition, a large number of studies have shown that in CC, GSK3β is involved in the regulation of the PI3K/Akt signaling pathway and the promotion of the malignant progression of CC cells 48,49 . This suggests that the regulatory role of USP14 in CC progression may be due to interactions with different key signaling pathways.…”
Section: Discussionmentioning
confidence: 91%
“…47 In addition, a large number of studies have shown that in CC, GSK3β is involved in the regulation of the PI3K/Akt signaling pathway and the promotion of the malignant progression of CC cells. 48,49 This suggests that the regulatory role of USP14 in CC progression may be due to interactions with different key signaling pathways. The pathway of USP14 action in CC may be a type of network rather than a single upstream and downstream pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of SCD1 was also found to be correlated with tumor grade and was associated with low overall survival in patients [ 167 ]. The association between high SCD1 expression in cancer tissue samples and poor clinical prognosis was also observed in bladder cancer [ 168 ], prostate cancer [ 169 ], pancreatic cancer [ 170 ], ovarian cancer [ 171 ], lung cancer [ 172 ], colorectal cancer [ 173 ], clear cell renal cell carcinoma [ 174 , 175 ], and cervical cancer [ 176 ]. A Swedish men study also showed an association between single-nucleotide polymorphisms in the SCD-1 gene and cancer death [ 59 ].…”
Section: Role Of Endogenously Synthesized Mufa In Cancermentioning
confidence: 99%
“…The final results showed that the expression of KLF9/SCD1 could regulate the Akt/GSK3-β signaling pathway in CC cells and affect the proliferation, invasion and EMT process of CC cells. This phenomenon can be suppressed by knocking out SCD1 ( 38 ). Studies have also shown that SCD1 can regulate the level of miR-1908, and its high expression levels can promote the proliferation and invasion of CC cells ( 59 , 102 ).…”
Section: Targeting De Novo Fatty Acid Synthesismentioning
confidence: 99%